The suitability assessment of the tree species in the urban parks and urban forest in Kediri City, East Java, Indonesia - Whisnu Febry Afrianto; SUSANTI INDRIYA WATI; TAUFIQ HIDAYATULLAH (Smujo International, 2021)
Abstract. Afrianto WF, Wati SI, Hidayatullah T. 2021. The suitability assessment of the tree species in the urban parks and urban forest in Kediri City, East Java, Indonesia. Nusantara Bioscience 13: 131-139. Kediri has several urban parks and an urban forest as green open space (GOS), which have essential roles in economical, social, aesthetical, and ecological aspects. Generally, urban trees provide ecosystem services, such as carbon sequestration, stormwater attenuation, energy conservation, habitat for wildlife, and air, water, and noise pollutants reduction. The present study aimed to (i) determine tree diversity in five urban parks and an urban forest in Kediri City and (ii) evaluate the suitability of tree species based on three indicators (silviculture, management, and aesthetic). This study was conducted in five urban parks and one urban forest in Kediri City. The suitability assessment was carried out through a literature review. The results showed that 29 tree species belonging to 17 families were found in the study sites, with the family Fabaceae being the most dominant one with five species. The number of exotic tree species (17) was higher than that of the native ones (12). The suitability assessment results showed that 21 tree species had a high score of 39-44, and only eight urban tree species had a medium score of 36-38. The urban parks and forests in Kediri were managed to conserve germplasm, recreation, and protection. Therefore, the shapes had to be clumped and lined. This study will contribute information to be used as guidance for urban tree management and policy framework.